Prototipe Kelas Pintar Berbasis Android Menggunakan Metode Rapid Application Development Di Universitas Bina Insani - Tiar Permana; Rully Pramudita (Ikatan Ahli Informatika Indonesia, 2024)
The concept of smart classrooms has become a solution to improve the efficiency of the teaching and learning process. However, there are still challenges related to classroom preparation and management, such as forgetting to turn off devices after use or leaving the room without locking the door. The aim of this research is to develop the BiU-Class application to remotely control devices in the classroom. The development method used is Rapid Application Development (RAD) to accelerate the development process. Testing results between the application and the devices show that the system works well, demonstrating that the Smart Classroom concept has the potential to address problems in education. However, its implementation is currently hindered by electrical issues that require further research. The developed application is considered easy to understand by users, thus having the potential for future development and use once technical issues are resolved.